Rente im Dritten Reich Die Reichsversicherungsanstalt für Angestellte 1933 bis 1945 - Erker, Paul (Berlin/Boston De Gruyter, 2019)
Scant research attention has addressed the role, significance, and function of the RfA in the maintenance and reformulation of the retirement insurance system in the Nazi society transformed by the ideology of the Volksgemeinschaft. For the first time, based on primary sources, this book presents a problem-oriented administrative history that investigates the place of the RfA in the National Socialist institutional structure.
German
Keywords: European history; 20th century history: c 1900 to c 2000; Fascism & Nazism; Modern administrative and institutional history; employment history; pension law development in the Nazi state; pension insurance during the Nazi era